Application of the Acoustic Impedance (AI) Seismic Inversion and Multi-Attribute Method for Reservoir Characterization in Bonaparte Basin - Maurin Puspitasari; Ambran Hartono; Egie Wijaksono; Tati Zera (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2021)
Research on the application of the acoustic impedance (AI) seismic inversion and multi-attribute method was conducted with the aim to characterize the reservoir in the Bonaparte Basin. The modeling which used in the acoustic impedance inversion seismic method is model-based. Meanwhile, the multi-attribute seismic method used log porosity that appliying the linear regression method and using the stepwise regression technique. Based on the result of the sensitivity analysis and analysis using the seismic inversion acoustic impedance method, the sandstone reservoir zone that has the prospect of hydrocarbons containing gas is located in the Northeast-Southwest part of the study area which in WCB-1, WCB-3 and WCB-4 well with the acoustic impedance values are in the range of 4,800 - 13,000 (m / s) * (g / cc), and the porosity values generated from the analysis using the multi-attribute seismic method are in the range of 5 - 16% in WCB-1 and WCB-4, 2 - 10% on WCB-3.